Reasonable top coal thickness for large cross-section open-off cut in lower-layer mining - Gao, Shigang; Du, Wengang; Liu, Yongliang; Chai, Jing; Gao, Dengyan; Ma, Chenyang; Chen, Jianhua (Frontiers in Earth Science, 2023)
The thickness of top coal is the main factor affecting the stability of the large cross section open-off cut under the goaf. The 1-2 lower 203 cross section open-off cut of the Huojitu Coal Mine was used as the background to investigate the top coal rational thickness of the large cross section open-off cut under the goaf in slicing mining. The top coal above the cut was simplified into a beam model to calculate its plastic zone range with the elastoplastic theory under the influence of the upper slicing mining and the lower slicing cut excavating. The deformation law of the top coal of the large cross section open-off cut under different top coal thicknesses was studied with both a simulation experiment and numerical simulation. The displacement, stress, and top coal structure of the surrounding rock of the cut were observed in situ using several observation methods. The results show that the plastic zone of the floor in the upper slicing face and the influence of the cut excavation are 2.02 m and 1.43 m, and the maximum plastic zone of the top coal is 3.45 m. A top coal thickness of more than 3.45 m is conducive to maintaining the stability of the large cross section open-off cut. The top coal of the cut can be divided into the roof-fall hazard zone and roof-fall warning zone according to the results monitored by distributed optical fiber. When the top coal thickness is 3.0 m, 3.5 m, and 4.0 m, the deformation law changes from an exponential deformation to a linear and then to a logarithmic relationship in the roof-fall hazard zone and from a linear to a logarithmic relationship in the roof-fall warning zone. When the thickness of top coal is 3.5 m and 4.0 m, the subsidence trend of the top coal visibly decreases, and the subsidence is only 56% and 39% of the subsidence of that of a thickness of 3 m. The deformation law of top coal measured using the DIC (Digital Image Correlation, DIC) is consistent with that of distributed optical fiber. The average thickness of the top coal reserved in the 1-2 lower 203 large cross section open-off cut is 4.0 m. The maximum surface subsidence of the top coal cut hole is 12 mm in the field monitoring. The maximum internal subsidence is 6 mm, and the maximum shed beam strain is –416 με. The deformation of the top coal is slight, indicating that the top coal thickness of 3.5–4.0 m is reasonable.